Personality and faecal cortisol metabolites levels of domestic cats (Felis silvestris catus) - Fukimoto, Naila Maui (2018)
The study of cat personality and behaviour can help minimize potential problems in the relationship between cats and their tutors and decrease relinquishment or maltreatment. Personality in animals is a promising area dedicated to studying characteristics of individuals that describe and account for temporally stable patterns of affection, cognition and behaviour traits. In general, people adopt cats according to their appearance, age or sex. Personality assessments can promote successful adoptions by identifying ideal animals for potential tutors. The American Society for the Prevention of Cruelty to Animals (ASPCA) has implemented a program called Meet Your Match® (MYM) which assesses the personality of shelter cats and the life style of adopters. With a better match between cat and tutor, the rate of animals being returned to shelters tend to decrease and cats welfare and adaptation in new homes tend to improve. To evaluate physiological stress and personality dimension, faecal cortisol metabolites (FCM) levels were measured and a modified MYM protocol was applied in two localities: a shelter and the tutors home. Our main goals were: 1) verifying the validity of personality dimensions used in a modified MYM assessment in a Brazilian cat shelter sample through an exploratory study of the psychometric properties of the protocol, as well as an exploratory factor and a cluster analysis; 2) verifying the correlation between personality and faecal cortisol levels; 3) checking if MYM assessment is consistent through change of localities; and 4) finding out how moving from the shelter to the tutors home affects faecal cortisol metabolites levels. We found evidence of validity of the modified MYM assessment based on internal structure to personality dimensions in this sample, although it presented a factorial structure that differs from the original assessment. No correlation was found between personality dimensions and FCM levels, corroborating the literature. There was a slight decrease of FCM levels in homes, but most subjects maintained their FCM levels, showing that cats can cope with stress in both environments the shelters and the tutors home. MYM personality assessment was consistent throughout the change of localities, which indicates that it is a good instrument to assess cat personality